The Development Of A 360-degree Evaluation Model Of Medical Curriculum With The Kirkpatrick Hierarchy Approach - Mia Kusmiati; Suhaila Sanip; Rafidah Bahari (Universiti Sains Malaysia, 2024)
Indexed by Scopus/MyCite